Visualisation of geo-tagged pictures in the web. (21st June 2011) - Carboni, Davide; Marotto, Valentina; Zanarini, Pietro
This work summarises a study of three different user interfaces for browsing geo-referenced pictures on websites. The subjects of this study are two widely used system like Panoramio and Flickr, and a new application develosped by the authors and called the 'Fractal View'. The study has been conducted by means of users' interviews and eye tracking.